Between Scrolling and Sharia: The Ethics of Ghadul Bashar Among Generation Z Students in the Age of Visual Media - Moch Risyad Abdillah; Ahmad Nurrohim; Mohd Rab (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to examine the construction of Generation Z's understanding of the concept of ghadul bashar, evaluate its implementation in the practice of using social media, and identify the complexity of ethical challenges that arise in the digital ecosystem. Theoretical framework: A theoretical framework integrating the principle of Ghadul Bashar in Islamic shari'a (QS. An-Nur 30–31) with the perspective of digital ethics and media behavior theory, to explain the interaction between religious normative values and the algorithmic logic of social media. Literature review: While Islamic ethical literature emphasizes self-discipline and visual control, studies of digital media show the dominance of algorithms, visual culture, and FOMO that tend to weaken such controls, thus indicating a tension between religious norms and contemporary digital practices. Methods: This study uses a qualitative approach with an exploratory design, through the extraction of empirical data from students as a representation of Generation Z, which is thematically analyzed to identify patterns of understanding and practice. Results: The findings show that there is a structural dilemma between the demands of shari'a and digital reality. The understanding of informants is heterogeneous, while key challenges include algorithmic pressure, automated scrolling behavior, normalization of visual content, FOMO, and the ambiguity of ethical boundaries in the digital space. Implications: Theoretically, this study expands the discourse of Islamic ethics in a digital context. Practically, this research offers an integrative approach based on Islamic digital literacy, self-reflection (muhasabah), optimization of content control features, and strengthening digital communities. Novelty: The novelty of this research lies in the synthesis between classical Islamic ethical concepts and algorithmic dynamics of social media, as well as the emphasis on Generation Z's lived experience in facing digital ethical dilemmas.